Measuring the Relationship Between Attitudes and Intentions to Participate in SLA Research: A Study of EFL Students at the School of Arts & Humanities of Meknés, Morocco - Laabidi, Hicham; El Harrath, Abdenbi (ELT in Focus, 2023)
This study was carried out to measure the relationship between undergraduate EFL students’ attitudes and behavioral intentions to participate in SLA research at the School of Arts and Humanities of Moulay Ismail University. This was a quantitative study that used descriptive-correlational design. The population of the study was all undergraduate EFL students at the School of Arts and Humanities of Moulay Ismail University. A validated Likert scale-based questionnaire was used to collect data from 115 participants selected through convenience sampling. Descriptive statistics such as percentages, means and standard deviations were used to measure students’ attitudes and intentions to participate in SLA research. While Spearman rank correlation, as a non-parametric test, was used to measure the relationship between attitudes and behavioral intention to participate in SLA research. The study found that EFL students have moderately positive attitudes towards participation in SLA research. Similarly, the study revealed that EFL students have a moderately positive intention to participate in SLA research. Spearman rank correlation yielded a coefficient of .703 indicating a strong positive correlation between attitudes and behavioral intention to participate in SLA research. The results of this study may be used as a basis for more research on attitudes towards participation in SLA research. Keywords: Attitudes, Behavior, Behavioral intention, SLA research, research participation.